The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1158/1538-7445.am2016-1201
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1201: Anti-B7-H3 antibody-drug conjugates as potential therapeutics for solid cancer

Abstract: Introduction: Monoclonal antibodies (mAbs) were generated via a target-unbiased approach based on intact cell immunization with cell lines, fetal progenitor cells, and cancer stem cells. An immunohistochemical (IHC) screen for cancer-specific candidates identified a panel of anti-B7-H3 (CD276) mAbs with highly differential tumor-versus-normal tissue binding. B7-H3 expression was observed in tumor epithelium as well as tumorassociated vasculature and stroma. Consistent with our findings, B7-H3 has been reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Using this approach, we identified B7-H3 as a cell surface protein with limited expression on normal tissues but overexpressed on the epithelium and tumor-associated vasculature in solid cancers. Validation studies showed that ligation of B7-H3 by several mAbs in our panel led to mAb internalization and antitumor activity toward B7-H3-expressing tumor cells when the mAbs were conjugated to auristatin (25). Based on these results, we selected a lead candidate mAb and sought to develop an ADC targeting B7-H3 for the treatment of cancer.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Using this approach, we identified B7-H3 as a cell surface protein with limited expression on normal tissues but overexpressed on the epithelium and tumor-associated vasculature in solid cancers. Validation studies showed that ligation of B7-H3 by several mAbs in our panel led to mAb internalization and antitumor activity toward B7-H3-expressing tumor cells when the mAbs were conjugated to auristatin (25). Based on these results, we selected a lead candidate mAb and sought to develop an ADC targeting B7-H3 for the treatment of cancer.…”
Section: Discussionmentioning
confidence: 88%
“…A pool of anti-B7-H3 mAbs was generated from a series of intact cell immunizations (13). The anti-B7-H3 mAb PRCA157 was selected as an ADC candidate from the pool of anti-B7-H3 mAbs based on its characteristics, including affinity, tumor versus normal tissue cross-reactivity profile, cynomolgus monkey B7-H3 cross-reactivity, cell internalization, and antitumor activity from screens as monomethyl auristatin E-based ADCs (25). PRCA157 was humanized by CDR grafting and fused to human C-kappa and gamma 1 constant regions, yielding the precursor MGA017 mAb, which retained the B7-H3 binding affinity of the parental murine mAb.…”
Section: Selection and Generation Of Mgc018mentioning
confidence: 99%